Transcription Factor KLF7 Promotes Osteoclast Differentiation by Suppressing HO-1 - Chen, Changhong; Hu, Fei; Miao, Shichang; Sun, Liping; Jiao, Yajun; Xu, Mingwei; Huang, Xin; Yang, Ying; Zhou, Rongkui (Frontiers in Genetics, 2022)
Background: Osteoporosis is a common orthopedic disease with high prevalence in patients older than 50 years. Osteoporosis is often detected only after the fracture and is hard to treat. Therefore, it is of great significance to explore the molecular mechanism of the occurrence of osteoporosis. Methods: The expression of Heme oxygenase-1 (HO-1) in people with different bone mineral density (BMD) was analyzed based on public databases. GenHacncer and JASPAR databases were adopted to search and verify the upstream transcription factor of HO-1. qRT-PCR, western blot and tartrate-resistant acid phosphatase assays were performed to explore the impact of HO-1 and Kruppel-like factor 7 (KLF7) on osteoclast differentiation. Chromatin immunoprecipitation (ChIP) assay confirmed the binding relationship between KLF7 and HO-1. Finally, Hemin, the agonist of HO-1, was applied in rescue assays, thereby verifying the mechanism of KLF7 modulating osteoclast differentiation by HO-1. Results: Bioinformatics analysis revealed that HO-1 was highly-expressed while KLF7 lowly-expressed in people with high BMD. Besides, a potential binding site of KLF7 was found on the promoter region of HO-1. ChIP assay further manifested the targeting relationship between HO-1 and KLF7.Western blot and TRAP staining unveiled that osteoclast differentiation was suppressed by HO-1, while facilitated by KLF7. Rescue experiments indicated that over-expressed HO-1 could reverse of the promoting effect of KLF7 on osteoclast differentiation. Conclusion: The study confirmed that osteoclast differentiation was promoted by KLF7 constraining HO-1, thereby facilitating osteoporosis. The cognation of the pathogenesis of osteoporosis was further enriched. New treatment could be developed on this basis.